FINANCIAL LITERACY CHALLENGES: THE CASE OF FILIPINO PUBLIC-SCHOOL TEACHERS - Casingal, Cyrus; Ancho, Inero (Universitas Brawijaya, Indonesia, 2021)
This study analyzed the Philippine public school teachers' financial literacy challenges. The data and results were gathered through online survey questionnaires and focused group discussions conducted in the school year 2019-2020. Twelve participants contributed to the FGD, while a total of 325 teacher respondents answered the online survey questionnaires. The results showed that the majority of the public-school teachers are struggling financially. That results in a controlled and limited financial lifestyle. Moreover, teachers unconsciously practice informal debt, which causes uncontrolled debt. Without proper knowledge and education to financial literacy, borrowing money becomes a lifestyle of every teacher in the country. Based on the findings, a financial literacy program must be included in every in-service training or division-wide teachers' mass gathering. The financial literacy program may be implemented by all participating schools where the study was conducted. Future research related to financial literacy programs may be conducted in basic education, colleges, and universities following the method used in this study.